STRATEGI PEMASARAN DAN INOVASI TERHADAP PENINGKATAN EKONOMI KELUARGA MASYARAKAT PESISIR (STUDI KASUS PEMBUATAN KRIPIK DAUN JERUJU DUSUN PALOH MERBAU KECAMATAN PERCUT SEI TUAN) - Syahrul Budiman; Mhd Amin; muhammad Irwansyah Hasibuan; Hayanuddin Syafri; Yuli Rosmawati Rambe (Politeknik Bisnis Indonesia, 2023)
Coastal Communities (Case Study of Making Jeruju Leaf Chips in Paloh Merbau Sub-district Percut Sei Tuan), either partially or simultaneously. The population in this study was the Coastal Community of Making Jeruju Leaf Chips in Paloh Merbau sub-district Percut Sei Tuan, the time of the study was from January to July 2022. The sampling technique used the opinion of Arikunto with a total of 40 people and the analytical method used was descriptive analysis method, analysis multiple linear regression, and hypothesis testing. The results of partial hypothesis testing (t test) show that Marketing Strategy (X1) and Innovation (X2) have a positive and significant effect on Economic Improvement, with the value of the Marketing Strategy variable tcount of 3.636 while t-table is 1.688 (tcount > from ttable). Innovation variable tcount is 3,081 while t table is 1,703 (tcount is greater than ttable). Meanwhile, for the Organizational Commitment variable, the value of tcount is 2.220 while ttable is 1.688 (tcount > from ttable). Simultaneous hypothesis testing results (F test) indicate that Marketing Strategy (X1) and Innovation (X2) have a positive and significant impact on improving the economy of the community in Coastal Communities (Case Study of Making Jeruju Leaf Chips, Paloh Merbau Hamlet, Percut Sei Tuan District, with a value of fcount is 10.510 while t table is 3.25 (Fcount is greater than Ftable).The results of the coefficient of determination (R2) can be seen that the Adjusted R square value is 0.328 or 32.8% indicating that Marketing Strategy and Innovation simultaneously contribute to Economic Improvement of 32.8%